O Porto nas navegações ultramarinas quinhentistas : embarcações e náuticos - Polónia, Amélia (2000)
This study aims to analyse the 16th century naval logistics of the city of Oporto and the nearby seaports of Leca and Matosinhos in order to: 1. Evaluate their importance, within the context of the Entre-Douro-e-Minho region in particular, and the country in general, both in terms of naval fleet and number of seamen; 2. Discuss the role of Leça and Matosinhos and their status as satellite ports of the city of Oporto; 3. Seek to establish the possible interactions between the borough's naval logistics and commercial dynamics.